The Human Being in Eastern Church Father’s and Al-Ghazali’s Philosophical Theology - Nur Serikovich Kirabaev; Olga Vasilievna Chistyakova (Religions, 2023)
The authors analyze two historical types of philosophical culture—the classical Eastern Patristics and Arab–Muslim medieval thought. They are united by the religious doctrine of man, which allows considering the intercultural and inter-theological nature of these traditions. In more particular terms, the article examines the understanding of the human being of the thinkers of Nicaea and post-Nicaea periods of Eastern patristics—Athanasius of Alexandria and Maximus the Confessor—and Abu Hamid al-Ghazali as the most profound representative of the Sufi philosophical–theological system of the Middle Ages. The authors highlight the philosophical, intercultural, and interreligious significance of the mentioned anthropological concepts. The article focuses on the comparability and consistency of the ideas of the Church Fathers and al-Ghazali. Particular attention is paid to Islam’s theoretical image of man as a caliph—a successor—of the Creator on the Earth. Comparative studies reveal the patristic vision of man, containing in himself the fullness of Divinity and humanity. The main points of the dyophysite Christian understanding of the God Incarnate in contrast to the monophysite currents of Apollinarianism are revealed. The depth of the Christological views of Athanasius of Alexandria and Maximus the Confessor is presented. Al-Ghazali’s doctrine of man is substantiated as a conceptual understanding of man’s place in the system of the world created by God, which is seen as a holistic and systematized doctrine of humanity in Muslim philosophy. Conclusions are made about the comparability and the presence of intersections between Eastern Christian, Byzantine, and Muslim types of thought.